Effect of dietary energy and protein on the production parameters of slaughter ostriches (Struthio camelus var. domesticus) - Viviers, Swys Francois (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.